The Reinvention of a Literary Space by Vassilis Alexakis. - Recuenco-Peñalver, María (My University, 2018)
In 2012, after a big operation on one leg, Vassilis Alexakis spends a month and a half on crutches at a hotel near the Parisian Luxembourg Garden. Just like the main character of his fourteenth and second to last novel, L’enfant grec, that he wrote then. The author seems to have the need to talk about space. Not only in this book, but in all his books, the author offers countless spatial references. Is it because of his health condition then, or is it because of his current (and for many years already) life divided in between two beloved countries, that Vassilis Alexakis needs to constantly speak about space? Is there a link between all the physical spatial references and the existential need of knowing where he is? Does his identity depend on his spatial location? With his literary combination of reality and fantasy, Alexakis might very well be reinventing space. His books could be the space in between, where he can freely just be: a Greek and a French author; narrator and character; in Greece or in France. A space in between just like the catacombs where we see the main character at the end of the book, depicted as the place where “la frontière entre le réel et l’imaginaire” is (page 307), or the space where he feels himself in every time he opens one of the volumes of his dear companion, the Grand Robert dictionary: “un espace qui n’appartient à aucun lieu, dépourvu d’addresse, qui flotte à la surface du temps comme le jardin de Callithéa” (page 281). The relation between Vassilis Alexakis and space is worthy to revise in this particular novel since as its main character states, “C’est un livre sur la vie et la mort […]. Sur la santé et la maladie, […] le mouvement et l’immobilité, le geste et la parole.¨
Keywords: Alexakis, Vassilis - Crítica e interpretación; Literatura francesa; Vassilis Alexakis; French; Self-translation; Modern Greek; Literature; Literary translation; Literary space